Inclusive Education Learning Management for Students with Disabilities (PDPD) in Junior High School - Montolalu, Steven S.; Rawis, Joulanda AM; Sumual, Shelty DM (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study aims to analyze the planning, implementation, and supervision of inclusive educational learning for students with special needs at SMP Negeri 1 Tomohon, as well as to identify the obstacles and efforts to overcome them. Using a qualitative approach, data were collected through observation, interviews, and document analysis. The findings show that inclusive learning planning still uses the regular curriculum and learning structure, without modification for students with special needs. Implementation has begun but is not yet optimal due to the absence of Special Education Teachers, limited facilities, and low teacher discipline. Supervision is carried out by the principal but remains limited due to a lack of specialized personnel. The main obstacles include the lack of professional teachers, unadapted curriculum, inadequate infrastructure, and inconsistent educator performance. Efforts to address these issues include recruiting trained staff, modifying the curriculum, and improving teacher discipline through supervision and policy enforcement. The study recommends strengthening planning based on assessment, encouraging teacher innovation, and improving school leadership and government support.